Legal Protection of Workers/Labor in Determining the Minimum Wage of West Java Province In 2023 Linked to Government Regulation Number 36 of 2021 Concerning - Sri Nurcahyani (Yayasan Ilomata, 2023)
With several current laws, legal protection is an attempt to safeguard the government or other authorities. Any person who works and is paid a salary or other sort of pay is a worker or laborer. Wages are the legal entitlements that employees and laborers have when they are paid by business owners or employers in the form of money. The purpose of this study is to ascertain how Government Regulation No. 36 of 2021 concerning Wages relates to legal protection for workers/laborers in setting the minimum salary for West Java province in 2023. The study's findings revealed that Government Regulation No. 36 of 2021 concerning Wages—which serves as the basis for determining the minimum wage—does not include the survey known as the Decent Living Needs (KHL), which was formerly conducted annually as required by Minister of Manpower Regulation No. 21 of 2016 concerning Decent Living Needs but is now only reviewed every five (five) years. There will no longer be a KHL survey following the passage of Law Number 11 of 2020 about Job Creation in conjunction with Government Regulation No. 36 of 2021 concerning Wages.